The association between different hypoglycemic regimens and postoperative diabetic macular edema after vitrectomy in the Japanese patients with proliferative diabetic retinopathy - Chunyan Lei; Chunyan Lei; Yun Zhang; Yun Zhang; Meixia Zhang; Meixia Zhang (Frontiers in Endocrinology, 2022)
PurposeTo study the association between different hypoglycemic regimens and postoperative diabetic macular edema (DME).MethodsA secondary analysis based on a retrospective cohort study.ResultsIn this secondary analysis, 124 eyes from patients with proliferative diabetic retinopathy (PDR) who underwent pars plana vitrectomy (PPV) between January 2008 and September 2012 were included. We found that compared with oral hypoglycemic medication, oral hypoglycemic medication plus insulin treatment revealed an insignificant relationship with postoperative DME (odds ratio [OR]=0.8, 95% confidence interval [CI]: 0.12-5.21, P=0.8167), only insulin treatment revealed a significant association with postoperative DME (OR=0.10, 95% CI: 0.01-0.84, P=0.0337) after adjusted age, sex. After adjusted age, sex, diabetes mellitus (DM) duration, glycosylated hemoglobin (HbA1c), the results did not have obvious changes (OR=0.61, 95% CI: 0.09-4.26, P=0.6187; OR=0.07, 95% CI: 0.01-0.65, P=0.0197). Furthermore, after adjusted age, sex, DM duration, HbA1c, hypertension, intraoperative retinal photocoagulation, vitreous hemorrhage, macular detachment, fibrovascular membrane, intraocular lens implantation and microincision vitrectomy surgery, the results were consistent (OR=0.66, 95% CI: 0.05-9.49, P=0.7621; OR=0.06, 95% CI: 0.00-0.81, P=0.0342). The same trend was observed in these adjusted models as well (p for trend was 0.0254, 0.0141, and 0.0311, respectively).ConclusionIn conclusion, our results of the secondary analysis should be interpreted as a significant association between insulin treatment and reduced risks of postoperative DME in Japanese PDR patients with PPV surgery, compared with oral medications. Well glycemic control with longstanding insulin therapy may be beneficial to reduce the risks of postoperative DME in PDR patients. Our investigation calls for large-scale and long-term prospective clinical studies for a full evaluation of the exact role of insulin in the progression of postoperative DME.